Foreign Policy as Pork-barrel Spending: Incentives for Legislator Credit Claiming on Foreign Aid. (August 2020) - Heinrich, Tobias; Peterson, Timothy M.
Foreign policy often creates geographically concentrated domestic benefits. A prominent example is the tying of development aid to purchases from the donor country. This feature of aid highlights the utility in examining foreign policy as an instance of pork-barrel politics. Considering tied aid in terms of legislators' incentives to provide constituent benefits, we argue that people will support an increase in foreign aid spending more when it would promote local economic activity, while opposing aid cuts more when reduced local economic output would result. Crucially, we also expect that people will support their state's US senator more when informed that the senator attempted to secure (or retain) locally beneficial funds. We find support for our expectations in a novel survey experiment of US citizens. Our results suggest that legislators' electoral incentives, and consequential local spending, can help explain the adoption of foreign policies despite national-level public disapproval.